COVID-19 Vaccine Willingness among African, Caribbean, and Black People in Ottawa, Ontario - Josephine Etowa; Bishwajit Ghose; Egbe Etowa; Charles Dabone (COVID, 2023)
Vaccines have been identified as a crucial strategy to control the spread of COVID-19 and reduce its impact. However, there are concerns about the acceptance of vaccines within African, Caribbean, and Black (ACB) communities. Based on a community sample of ACB people in Ottawa, Ontario (n = 375), the current study aimed to use logistic regression analysis and identify factors associated with COVID-19 vaccine willingness. A multivariate analysis shows that ACB people who believed that the ACB population is at a higher risk for COVID-19 were more likely to be willing to receive the vaccine compared to those who did not (OR = 1.79, p < 0.05). ACB people who had received at least one dose of the COVID-19 vaccine were more likely to be willing to receive it in the future (OR = 2.75, p < 0.05), and trust in government COVID-19 information was also positively associated with vaccine willingness (OR = 3.73, p < 0.01). In addition, English-speaking respondents were more willing to receive the vaccine compared to French-speaking respondents (OR = 3.21, p < 0.01). In terms of socioeconomic status, ACB people with a post-graduate degree (OR = 2.21, p < 0.05) were more likely to report vaccine willingness compared to those without a bachelor’s degree. Based on these findings, we discuss implications for policymakers and directions for future research.